Cartographies on an emergency: monitoring Ligustrum lucidum invasion in the metropolitan Sierras Chicas of Córdoba, Argentina (2002-2020) - Boccolini, Sara María (Ateliê Geográfico, 2025)
Invasive exotic vegetation poses a significant threat to ecosystems biodiversity conservation. Ligustrum lucidum (glossy privet) stands out as a prominent invasive tree species across ecosystems worldwide. The Chaco Serrano district in South America is one of the areas most affected in Argentina, particularly the metropolitan Sierras Chicas (Córdoba), which are home to Argentina's second most populous metropolitan area. Consequently, accurate and up-to-date information on L. lucidum invasion in that region is crucial for much needed management and restoration policies. I present a novel methodology to monitoring this invasion at regional scale, while generating local data with minimal use of resources. Calculating NDVI levels on Landsat imagery, I built detailed cartography spanning 20 years, showing that the affected area has increased over 10 times, affecting peri-urban areas and natural reserves. Moreover, I identified four sub-regions with different invasion patterns due to local environment and urbanization. The results prove valuable in database updates, raising awareness, diagnostic and local-control strategies, and are readily replicable in areas with comparable conditions.